Penerapan Model Pembelajaran Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV UPTD SD Negeri 46 Parepare - Novi Aswindah; Zaid Zainal; Abdul Hakim (Lembaga Yasin AlSys, 2026)
The low mathematics learning outcomes of fourth-grade students who had not yet met the learning objective achievement criteria indicate the need to implement a learning model that can improve the quality of the learning process and learning outcomes. This study aims to analyze the implementation of the Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) learning model in improving the learning process and students’ mathematics learning outcomes on fractions. The study employed a qualitative approach with a classroom action research design focusing on the learning process and students’ learning outcomes. The research subjects consisted of one teacher and 21 fourth-grade students at UPTD SD Negeri 46 Parepare. Data were collected through observation, tests, and documentation and were subsequently analyzed based on the development of teacher activities, student activities, and learning outcome mastery in each cycle. The results showed that in Cycle I, teacher and student activities were classified as adequate, while learning outcome mastery was still classified as poor. In Cycle II, teacher activities improved to the good category, student activities remained in the adequate category, and learning outcome mastery improved to the adequate category. Following corrective actions in Cycle III, teacher activities, student activities, and learning outcome mastery all reached the good category. This study concludes that the implementation of the ARIAS learning model can improve the learning process and students’ mathematics learning outcomes on fractions. These findings provide the practical implication that the ARIAS model can be used as an alternative learning model to increase student engagement and the achievement of mathematics learning outcomes in elementary schools.